Managing Institutional Trust and Policy Reform: Governance Strategies for Romania’s Law Enforcement and Social Protection Systems under SDG 16.6 - Cristian Gabriel IANC (Revista de Management Comparat International)
Institutional trust and policy reform are two essential elements of governance systems in law enforcement and social protection. This study explores how Romania is guiding these sectors in a way that meets the requirements of Sustainable Development Goal (SDG) 16.6 (development of effective, accountable and transparent institutions). By employing a mixed-methods methodology, the study combines survey evidence about the public perspective on institutional trust, the effectiveness of reforms and systemic obstacles with a comparative policy analysis concerning how Romania respects European governance standards. Yet, the country still faces hurdles in the areas of institutional inefficiency, corruption, insufficient resource allocation, and public distrust of governmental reform. As shown in the “Views from the Field” section of the report, survey data indicates that there is generally low confidence in the effectiveness of key policies, with respondents citing corruption, racial discrimination, and lack of training as the most significant barriers that inhibit effective governance. Furthermore, the study highlights a divide between law enforcement and social protection mechanisms, highlighting the need for integrated policy efforts. In response to these concerns, the research suggests governance strategies concentrating on institutional accountability, resource conjugation, improved community policing, and cross-sector collaboration. Assessing the impacts of individual policies and improving the related policy coherence and transparency in Romania will strike a balance between what people expect from a well-functioning state and the actual performance of the institutions, leading towards a more resilient and inclusive governing model. Such insights help advance the general debate on policy management, public-sector trust, and sustainable governance reform in the European and global context.